Great Expectations: Understanding the Gap Between Practitioner Expectation and Academic Output in Understanding Public Sector Reform - Dion Curry (International Research Society for Public Management, 2015)
This paper examines the potential expectations gap between what public administration academics deliver in terms of research on public sector reform and what public sector practitioners see as necessary to understand public sector reform. It draws on a large-scale survey of public sector executives in ten European countries, a survey of all European public administration academics and an interview programme with public sector trade union representatives and consultants. The findings show that there is a gap between how academics perceive public sector reform and how practitioners view public sector reform. More interestingly, there is also a gap in how academics view public administration as a discipline. Academics’ expectations about the discipline do not line up with what they see the discipline producing, resulting in an internal perceptions gap that affects the usefulness of public administration research. The key point to take away from this research is a need for academics, in their research and their practice, to be more realistic about what academic research can and should do. It is important that academics are aware of what their research is looking to accomplish, whether it can accomplish this, and how that fits into a practitioner perspective about what is necessary in practice.